The incidence rate of metastasis from the primary cutaneous squamous cell carcinoma: A literature review - Badr Mohammed F. Alotaibi; Mohammed A Kilani (Wolters Kluwer Medknow Publications, 2019)
Background: Cutaneous squamous cell carcinomas (cSCCs) are the second highest nonmelanoma skin cancer, commonly targeting the head and neck region. Owing to its rising annual incidence, the actual rate of metastasis from the primary cSCC is needed to be investigated separately to develop more efficient management plans, hence nobly decreasing the incidence rate of metastasis overall. Materials and Methods: We conducted a literature review about the incidence rate of metastasis from the primary (or de novo) cSCC, based on two popular databases (PubMed and Cochrane), excluding different-purpose serving articles, for example, unrelated outcomes, case series, and case reports. Results: The mean incidence rate of metastasis from the primary cSCC is 10% (1.2-16.5). The least mean tumor size reportedly associated with regional and distant metastasis was 1.11 cm, and the least median thickness was 3 mm deep. Most of the metastatic tumors were of T1 stage before metastasis, and all metastases reported in the literature had more than one risk factor at a time. The mean follow-up duration was 4 years. Discussion: About half of the included literature carried a suspicion of selection bias, which threatens both their internal validity by overestimating the actual rate of metastasis and their external validity by seizing the reproducibility of the current evidence. Almost 85% of the metastasis was reported in the regional lymph nodes, while only a few cases involved distant anatomies at the time of diagnosis. This was consistent with other separate literatures. Conclusion: The mean incidence rate of metastasis from the primary cSCC tumors in our literature review is 10%, which is relatively higher than what was reported before in similar reviews. However, a large prospective study needs to be conducted to control and follow the involved prognostic factors, stratify them according to their risk factors, and minimize the risk of the previously reported bias in other reviews.